STRES DAN KEPUASAN KERJA, DAMPAKNYA TERHADAP KINERJA KARYAWAN KONTRAK - Rozi, M. Fatkhur (Fakultas Ekonomi, UIN Maliki Malang, 2006)
This research examines how stress affect job satisfaction and employees performance. Stress in this research consist of work stress, group stress, financial stress, and family stress, where is fourth variable of stres affect job satisfaction and employees performance either through indirect and also direct. The research using data from a survey of 117 contract employees in Batu police Pamong Praja office use path analysis. The research finding that work stress, financial stress, and family stress affect performance either through direct and also indirectly through job satisfaction. As for group stress not be found to have influence do well by job satisfaction and performance. The research implication to organization studied furthermor.